2012
DOI: 10.1007/s11999-012-2369-5
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided Injections for de Quervain’s Tenosynovitis

Abstract: We found ultrasound-guided injections to be useful for treatment of de Quervain's tenosynovitis. Our success with ultrasound-guided injections was slightly better than that reported in the literature and without adverse reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
83
2
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 31 publications
0
83
2
6
Order By: Relevance
“…McDermott JD et al, reported in 2012 that at a follow up of 6 weeks, no complications were noted and 36 of the 37 wrist (97%). However 14% of wrist had recurrence of symptoms [17] This is in contrast to our study where 2 patients had recurrence of symptoms which relieved with another injection of Triamcinolone acetonide. Mohsin Mardani Kivi et al [22] conducted a prospective study over 67 patients.…”
Section: Discussioncontrasting
confidence: 95%
“…McDermott JD et al, reported in 2012 that at a follow up of 6 weeks, no complications were noted and 36 of the 37 wrist (97%). However 14% of wrist had recurrence of symptoms [17] This is in contrast to our study where 2 patients had recurrence of symptoms which relieved with another injection of Triamcinolone acetonide. Mohsin Mardani Kivi et al [22] conducted a prospective study over 67 patients.…”
Section: Discussioncontrasting
confidence: 95%
“…Retrospective and prospective cohort studies report improvements in most patients, but often over long time periods [6,11,16].…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of these new treatments, combined with the needle tenotomy techniques, have been made possible by the ability to visualize the degenerative tendon, perform percutaneous needling of the tendon and accurately place the injectate into the desired area. While [79] Acromioclavicular joint [80] Glenohumeral joint [81] Biceps tendon sheath [13] Aspiration/lavage of calcific tendinitis [68] Elbow Medial and lateral epicondyle [82] Elbow joint [83] Hand/wrist Carpal tunnel [84] De Quervain's tenosynovitis [85] Carpometacarpal and trapeziometacarpal joint [86] Trigger finger [87] Scaphotrapeziotrapezoid joint [88] Distal radioulnar joint [89] Lower extremity…”
Section: Musculoskeletal Medicinementioning
confidence: 99%